2007
DOI: 10.3324/haematol.11556
|View full text |Cite
|
Sign up to set email alerts
|

K-CL co-transport plays an important role in normal and   thalassemic erythropoiesis

Abstract: Background and ObjectivesCell volume changes are hallmarks of both cell maturation and apoptosis, and are paralleled by modulation of membrane ion transport pathways. We evaluated the possible role of K-Cl co-transport (KCC) in both normal and β-thalassemic erythropoiesis in vitro. Design and MethodsWe studied the effects of the KCC inhibitor, DIOA, on cell proliferation and differentiation, on expression of KCC mRNA and polypeptides, and on expression of cell cycle and apoptosis genes in in vitro liquid-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…35 Uncontrolled activation of the KCC has been reported in patients with sickle cell anemia and beta-thalassemia in whom pathological RBC dehydration is abundant. 36,37 Our observations show that this is also the case in the CHC patient's RBC. As for most ion transport systems, the activity of the KCC in normal RBC is down-regulated in response to cooling.…”
supporting
confidence: 52%
“…35 Uncontrolled activation of the KCC has been reported in patients with sickle cell anemia and beta-thalassemia in whom pathological RBC dehydration is abundant. 36,37 Our observations show that this is also the case in the CHC patient's RBC. As for most ion transport systems, the activity of the KCC in normal RBC is down-regulated in response to cooling.…”
supporting
confidence: 52%
“…Embora com menor conteúdo intracelular de Hb, hemácias talassêmicas podem apresentar valores de densidade tanto menores quanto maiores que hemácias normais 6,94 .…”
Section: Fisiopatologiaunclassified
“…Despite extensive knowledge of the molecular defects causing β-thalassemia, less is known about the mechanisms responsible for the associated ineffective erythropoiesis and reduced red cell survival (1)(2)(3)(4)(5)(6)(7). Increased levels of reactive oxygen species (ROS) have been reported to contribute to the anemia of β-thalassemia, although the effects of ROS have not been fully defined (1,(2)(3)(4)(5)(6)(7)(8). Exogenous anti-oxidant molecules might represent complementary therapeutic strategies to counteract the toxic effects of ROS in β-thalassemia.…”
Section: Introduction:-mentioning
confidence: 99%
“…5(7), 1190-1194 1191 have been shown to beneficially affect in vivo β-thalassaemic red cell features and/or thalassaemic ineffective erythropoiesis in vivo. (3)(4)(5)(6)(7)(8) Recent studies have shown that Resveratrol is a ribo-nucleotide reductase inhibitor, much more effective than hydroxyurea (HU), a molecule that has been used clinically as therapeutic agent for the treatment of Sickle cell anaemia, a haemoglobinopathy characterized by the polymerization of a mutated form of adult haemoglobin (HbS) leading to erythrocyte sickling which plays an important part in the disease morbidity. Hydroxyurea has proven its clinical benefit as it can increase fetal haemoglobin (HbF) levels in the red cells of sickle cell patients inhibiting HbS polymer formation.…”
Section: Introduction:-mentioning
confidence: 99%